IMPLUSE BUYING OLEH PROMOSI BUY 1 GET 1 PADA PELANGGAN KEDAI KOPI KETJE BANDAR LAMPUNG - Defia Riski Anggarini; Berlintina Permatasari (Jurnal Bisnis Darmajaya, 2020)
The purpose of this study was to examine the effect of buy one get one promotion through direct promotion and online media promotions on impulse buying in Ketje Bandar Lampung coffee shop customers. The number of respondents in this study were 100 respondents. Analysis of the data used is multiple linear regression analysis using the SPSS 25.0 program. The results of the study prove that the buy one get one promotion which is carried out through direct promotions has a positive and significant effect, while for online media promotions the positive and insignificant effect on impulse buying that occurs in Kedai Kopi Ketje Bandar Lampung.Keywords: Promosi buy one get one, Direct Promotions, Online Media Promotions, impulse buying